2016
DOI: 10.1111/jocn.13411
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life, sense of coherence and leisure‐time physical activity in women after an acute myocardial infarction

Abstract: Tailoring women after an acute myocardial infarction about lifestyle changes must include knowledge about the benefits of leisure-time physical activity, and that even a small amount of activity is associated with a better health-related quality of life. The utmost important assignment is to motivate the women for regular physical activity in their leisure-time. Older women need special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In comparisons with previous Norwegian studies, the mean SOC-13 score found in this study was slightly lower than in a population of women after myocardial infarction 46 and higher than in a sample of patients with musculoskeletal pain, 47 consistent with the lower SOC-13 scores for patients with Abbreviation: B, unstandardized estimated regression coefficient. * Adjusted for sex, age groups, multimorbidity, rehabilitation urgency, marital status, education, smoking, urbanity, pain/discomfort, depressive symptoms, and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…In comparisons with previous Norwegian studies, the mean SOC-13 score found in this study was slightly lower than in a population of women after myocardial infarction 46 and higher than in a sample of patients with musculoskeletal pain, 47 consistent with the lower SOC-13 scores for patients with Abbreviation: B, unstandardized estimated regression coefficient. * Adjusted for sex, age groups, multimorbidity, rehabilitation urgency, marital status, education, smoking, urbanity, pain/discomfort, depressive symptoms, and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…In the last decade, some observational and survey studies [9][10][11][12][13][14][15], randomized clinical trials [16][17][18] and evaluations of cardiac rehabilitation programs [19][20][21] reported a positive association between HRQL and physical activity in patients with ischemic heart disease (IHD). Nine reports identified the recruited patients as having coronary heart disease [9,10,[12][13][14][16][17][18][19], one meta-analysis included IHD patients who also had a myocardial infarction (MI) or angina [20], and the others included patients having a specific diagnosis like MI [11,15] or ischemic heart failure [21]. These studies used 50-50 generic [10-13, 18, 19] and IHD-specific HRQL questionnaires [9,[14][15][16][17]21], applied different strategies to measure physical activity: instruments with validation [11,[16][17][18][19], without validation [9,10,13,15], both [12,14] or with objective parameters …”
Section: Introductionmentioning
confidence: 99%
“…Nine reports identified the recruited patients as having coronary heart disease [9,10,[12][13][14][16][17][18][19], one meta-analysis included IHD patients who also had a myocardial infarction (MI) or angina [20], and the others included patients having a specific diagnosis like MI [11,15] or ischemic heart failure [21]. These studies used 50-50 generic [10-13, 18, 19] and IHD-specific HRQL questionnaires [9,[14][15][16][17]21], applied different strategies to measure physical activity: instruments with validation [11,[16][17][18][19], without validation [9,10,13,15], both [12,14] or with objective parameters [21], and included mostly cardiac patients in general. Therefore, the robustness of the evidence for a physical activity and HRQL dose-response gradient in patients with IHD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Walking regularly is one strategy for continuing to be active late in life (Guell, Shefer, Griffin, & Ogilvie, ). Among other cardiac patients, leisure‐time physical activity even at a low level can improve health‐related quality of life (Lovlien, Mundal, & Hall‐Lord, ). As a result, going for walks is an aspect that clearly became apparent and that was remarkably important for the patients in this study.…”
Section: Discussionmentioning
confidence: 99%